Nickel phosphide based hydrogen producing catalyst with low overpotential and stability at high current density. (10th March 2019) - Chen, Weiwu; Mishra, Ishwar Kumar; Qin, Zhaojun; Yu, Luo; Zhou, Haiqing; Sun, Jingying; Zhang, Fanghao; Chen, Shuo; Wenya, Gideon Evans; Yu, Ying; Wang, Zhiming M.; Song, Hai-Zhi; et al.
Abstract: Hydrogen has promise as a good future alternative to fossil fuels. Electrochemical water splitting is an environmentally friendly way to produce hydrogen, but high overpotentials and cost are the main limitations to the application of electrocatalysts in large-scale hydrogen production. Here, an inexpensive catalyst composed of Ni5 P4 /NiP2 nanoparticles on Ni5 P4 /NiP2 nanosheets was prepared by a simple chemical vapor deposition method to increase the active catalytic sites. This nickel phosphide exhibits an overpotential of 35 mV at a current density of 10 mA cm −2 in an acidic condition, outperforming other reported nickel phosphides. Additionally, it shows great stability at a high current density of 1200 mA cm −2, which is very important for large-scale applications. Furthermore, this sample shows pH universality, with good performance in both acidic and alkaline electrolytes. This work advances nickel phosphide as an efficient catalyst for the hydrogen evolution reaction in water splitting.